The Changing Face of Economics? Ethical Issues in Contemporary Economic Schools as a Consequence of Changes in the Concept of Human Nature - Horodecka, Anna (Annales. Etyka w Życiu Gospodarczym, 2015)
The last financial crisis combined with some recent social trends (like growing inequality or environmental problems) inspired many contemporary economists to the re-evaluation of actual economic knowledge in the search for solutions to these problems. Modern economic schools (especially heterodox ones) stress the meaning of ethical issues in economics more often. The thesis of the paper is that this revival of the ethical face of present economics depends very strongly on the changing assumptions of human nature within economics and other disciplines which work alongside economics, such as social psychology or business ethics, for instance. In order to prove the thesis, the paper provides an evaluation of current economic schools, especially within the heterodoxy, in search of their ethical aspects, and presents them as a result of the changing assumptions about human beings within those schools. This ethical dimension of human beings manifests itself in different ways, which can be perceived as a result of it being based on different ethical schools and different psychological and philosophical assumptions about human nature. Therefore, the paper also considers the current developments of the view on human beings in contemporary schools of economic ethics.